Análisis de la calidad de absorción visual de las unidades del paisaje del páramo de la laguna de anteojos del Parque Nacional Llanganates, propuestas de conservación, 2023. - Jácome Ocaña, Edgar David (2023)
This research project was developed with the purpose of establishing the quality and visual fragility of the components that make up the Páramo Units in the spectacled lagoon located in the Llanganates National Park in the province of Cotopaxi. A methodology focused on the identification of landscape units was applied, based on the guidelines determined by the Bureau of land Management (BLM) method for determining visual quality, visual absorption quality (CAV) and subsequently fragility. and visual sensitivity. An approach of qualitative values was established, which were identified through photographs that allowed to give value to each one of the criteria and components established for the visual evaluation of the landscape through the analysis of the registered photographs of the area under study. As results, it was established that the lagoon of glasses has a high visual quality with a statistical value of 22, indicating that the landscape has unique and outstanding features, its visual absorption capacity within the area was located in class II, with a value of 24.17, determining that the fragility of the landscape is medium and shows areas with regeneration capacity with medium potential, this is due to activities of anthropogenic origin that have modified the conditions of the landscape units, presenting a class I fragility with a value of 27, presenting a high fragility, while for the visual sensitivity of the landscape the most prevalent is Class 3, determining that they are areas of medium or high quality and variable CAV, which can be incorporated into the previous ones when circumstances so require. advise. It is concluded that there is a need to implement landscape conservation and management activities, and it is necessary to establish a conservation plan for the area.